EARTHQUAKE HYPOCENTER RELOCATION ANALYSIS IN THE MAMBERAMO FAULT AREA, PAPUA, INDONESIA AND SURROUNDING USING THE DOUBLE DIFFERENCE METHOD - Redoks Wellung, Marcelo
The Mamberamo Fault Zone which is located in the North Papua basin has a tectonic setting that was formed due to the subduction of the Australian plate under the Pacific plate and the Halmahera plate. Mechanistically, the Mamberamo Fault Zone is a fault system thrust belt, this condition causes a relatively high level of seismicity at shallow depths in northern Papua. The distribution of earthquake hypocenters can be used as a reference to understand the potential hazard and risk of an earthquake. However, the initial results of the hypocenter have a high degree of uncertainty especially at the focal depth of the earthquake, causing low accuracy in determining the earthquake hypocenter in the Mamberamo area. Hypocenter relocation can be used to increase the accuracy of earthquake hypocenters. This study aims to relocate the hypocenter of the earthquake in the Mamberamo Fault area, using P and S wave arrival time data from the BMKG earthquake catalog for the period 1 January 2018 – 31 June 2022. The relocation method used in this study is the Double Difference by using software hypoDD. Data events which are used amount to 2348 events, using the updated AK135-F speed model using software Velest 3.1, then relocation was carried out and the results of relocation were 1575 events. The distribution of relocation results shows changes in the hypocenter at relatively shallow depths with distribution events focused on 5 segments of Mamberamo Fault Zone.Land earthquake activity is seen to be significant in the southern part of segment Makai and Tuira while earthquakes in the water area are more common in the northern part of segment Toarim, Mawe and Djanggur. The slope pattern in segment Makai and Toarim are identified in the vertical sections A-A' and D-D'. The relocation results obtained can improve the accuracy of the hypocenter location, the geometry model of the Mamberamo Fault Zone and also the potential risk of earthquakes that could occur in the future.